The glycosylated haemoglobin A1c and albuminuria of patients with type 2 Diabetes in The Republic of Srpska: a cross sectional study - Stanivuk, Ljiljana; Mirjanić-Azarić, Bosa; Vasiljevic, Nađa (Vojnosanitetski pregled, 2021)
Background: Glycosylated haemoglobin (HbA1c) is currently the gold standard for glucose monitoring in patients with diabetes. The aim of the present study was to examine the level of success in implementing international guideline targets with regard to glycaemic control in patients with type 2 Diabetes in The Republic of Srpska. This study also aimed to determine the association of albuminuria with glycaemic control and lipid levels in this patient population. Methods: Participating diabetic patients were those registered in the project titled ’’Estimation of the quality of glycoregulation and presence of vascular complications in persons with Diabetes in The Republic of Srpska.” The study was conducted as a cross-sectional study, including 1037 patients. The HbA1c was determined by a turbidimetric inhibition immunoassay used Roche Diagnostics. Total cholesterol, triglycerides, LDL-C, and HDL-C were determined by reagents from Roche Diagnostics (Roche Diagnostics, Mannheim, Germany) as well as albumin and creatinine in the urine. Results: Mean value for HbA1c was 7.35±1.61% (57± 18 mmol/mol). The 49.46% of all participants achieved target values of HbA1c ( <7% or 53 mmol/mol) and 40.30% had albumin to creatinine ratio (ACR) <30 mg/g. When the patients were divided according to HbA1c (with HbA1c <7% and HbA1c ≥7.0% ) the ACR values were different among these groups (39.00 vs. 79.50, p<0.001). Also, we found no significant difference with respect to lipid status between the groups. Conclusion: Patients with type 2 Diabetes in The Republic of Srpska, in a large percentage, did not meet targets for glycaemic control. Improvements are necessary in treatment and maintenance of this disease process to ensure achievement of goals in management of diabetes, which in turn would decrease longstanding complications of type 2 Diabetes. Key words: type 2 Diabetes, HbA1c, albuminuria, lipids.